Recent passive technologies of greenhouse systems: a review - Harjunowibowo, Dewanto; Cuce, Erdem; Omer, Siddig A.; Riffat, Saffa B. (2016)
There are 130 countries produces greenhouse vegetables commercially with more than 1.1 million acres in 2016. Most of the greenhouses deal with high operating costs due to the great energy needs. The high heat loss because of the greenhouse envelope material is responsible for the high energy demand in greenhouses. Nevertheless, each area having a specific need which affects to the energy level and conventional greenhouse technologies tend to have poor U-values. It causes energy for heating is very dominant up to 85% of the total greenhouse energy demand in cold climates countries. While, for the hot climate countries the energy for cooling is more prevalent. Therefore, this paper presents the latest technological developments used in greenhouses in various countries used to control the microclimate in the greenhouse focusing on passive techniques. It is found that PCM recently used to provide heating and cooling for Mediterranean climate. Moreover, closed greenhouse concept based system for Northern climatic improves the reduction energy demands by 80% with a potential payback of 6 years. Additionally, for most countries double glazing envelopes to be the most frequently powerful to increase the greenhouse performance.